2013
DOI: 10.1021/ef401716h
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Upgrading of Athabasca Bitumen Using Multimetallic Ultradispersed Nanocatalysts in an Oil Sands Packed-Bed Column: Part 1. Produced Liquid Quality Enhancement

Abstract: Conventional crude oil production is declining, while the consumption of petroleum-based fuels is increasing. Therefore, bitumen and heavy oil exploitation is steadily growing. However, in the present context, heavy oil and bitumen exploitation processes are high-energy and water-intensive and, consequently, have significant environmental footprints because of the production of gaseous emissions, such as CO 2 , and generating huge amounts of produced water. In situ catalytic conversion or upgrading is a promis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…For instance, Nassar et al [96] was the first to propose in-situ upgrading of heavy oil by adding nanocatalysts in combination with SAGD ( Figure 15). Then, in order to investigate the effect of reaction severity and nanocatalysts on solid and gaseous products, Hashemi et al [97] studied for the first time in situ upgrading of Athabasca bitumen using Ni-W-Mo nanocatalysts in a continuous flow mode. The results showed that nanocatalysts bettered the quality of Athabasca bitumen by improving the bitumen properties such as decreasing the density, viscosity and microcarbon residue.…”
Section: Feasibility Studymentioning
confidence: 99%
“…For instance, Nassar et al [96] was the first to propose in-situ upgrading of heavy oil by adding nanocatalysts in combination with SAGD ( Figure 15). Then, in order to investigate the effect of reaction severity and nanocatalysts on solid and gaseous products, Hashemi et al [97] studied for the first time in situ upgrading of Athabasca bitumen using Ni-W-Mo nanocatalysts in a continuous flow mode. The results showed that nanocatalysts bettered the quality of Athabasca bitumen by improving the bitumen properties such as decreasing the density, viscosity and microcarbon residue.…”
Section: Feasibility Studymentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Because of their special and unique properties, nanoparticles are able to improve the mobility of oil under reservoir conditions and may be used as adsorbents/catalysts for 3 enhancing the upgrading and recovery of heavy oil. 5,11,13,14,22,23 The small size of the nanoparticles (between 1 and 100 nm) allows these particles unimpeded transport and a good dispersion ability through porous media, without risk of blocking the pores. 13 Further, the high ratio of the surface area/volume of the nanoparticles as well as their surface functionality makes them good adsorbents for heavy polar hydrocarbons in crude oils, such as asphaltenes.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, as proven by the studies above, once asphaltene compounds are adsorbed on the reservoir rock surface, wettability is altered to an oil-wet state until an effective treatment for asphaltene desorption is applied. Recently, nanoparticles have shown high potential for in-situ applications in the areas of inhibition of different types of formation damage (Franco, Nassar, Ruiz, Pereira-Almao, & Cortés, 2013c;Hashemi et al, 2015;Kazemzadeh, Malayeri, Riazi, & Parsaei, 2015a;Nassar, Betancur, Acevedo, Franco, & Cortés, 2015a;Shayan and Mirzayi, 2015;Zabala et al, 2014), enhanced oil recovery (Ehtesabi, Ahadian, & Taghikhani, 2014;Giraldo, Benjumea, Lopera, Cortés, & Ruiz, 2013a;Hashemi, Nassar, & Almao, 2014a;Hashemi, Nassar, & Pereira-Almao, 2012;Hashemi, Nassar, & Pereira Almao, 2013a;Hosseinpour, Mortazavi, Bahramian, Khodatars, & Khodadadi, 2014;Karimi et al, 2012;Kazemzadeh et al, 2015b) and heavy and extra-heavy oil upgrading (Franco et al, 2013b;Franco et al, 2014;Franco et al, 2015;Hamedi Shokrlu and Babadagli, 2013;Hosseinpour, Khodadadi, Bahramian, & Mortazavi, 2013;Hashemi, Nassar, & Pereira Almao, 2013b;Hashemi, Nassar, & Pereira Almao, 2014b;Mora, Franco, & Cortés, 2013;Nassar et al, 2015b;Nassar et al, 2012). Regarding the asphaltene-related problems, nanoparticles can restore wettability from an oil-wet state to a waterwet state (Giraldo et al, 2013a;Karimi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Also, regarding asphaltene precipitation/deposition, nanoparticles can selectively adsorb asphaltenes from large asphaltene aggregate systems, leading to the reduction of the mean asphaltene aggregate size, which subsequently decreases the probability of asphaltene precipitation and deposition (Nassar et al, 2015a;Zabala et al, 2014). In thermal processes, such as insitu combustion, once asphaltenes are adsorbed on the nanoparticle surface, aquathermolysis or thermolysis, a catalytic cracking of the asphaltene molecule, can occur, leading to the formation of new and lighter compounds that would promote the in-situ upgrading of heavy and extra-heavy oils (Franco et al, 2013b;Franco et al, 2014;Franco et al, 2015;Hamedi Shokrlu and Babadagli, 2013;Hashemi et al, 2013b;Hashemi et al, 2014b;Mora et al, 2013;Nassar et al, 2015b;Nassar et al, 2012;Nassar et al, 2011a). However, the re-use of nanoparticles and the changes in their intrinsic properties after asphaltene adsorption are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%